IMPLEMENTASI PENDEKATAN PEMBELAJARAN KONTEKSTUAL DALAM PERKULIAHAN BAHASA INGGRIS LANJUTAN SEBAGAI UPAYA PERBAIKAN KESALAHAN KONSEPSI DAN PENINGKATAN HASIL BELAJAR MAHASISWA - Agus Priadi (Universitas Bina Sarana Informatika, 2011)
The objectives of this action research were to describe the students’ prior knowledge profile, to modify theirmisconception into scientific concept, to improve their scientific attitude, to improve the quality of learningoutcome and to describe responses of 30 students of Administration Management at semester II in academicyear 2010/2011 of ASM BSI Jakarta towards the teaching of Advanced English by using contextual approach.The data about prior knowledge profile, misconceptions and learning outcome of the students were collectedby using test, while those of scientific attitude by using questionaire method, the students activity byobservation, and the students responses by questionaire and interview. The data was analyzed descriptivequalitatively. The findings showed that: (1) at the first cycle: 33.93% of the students’ prior concept was aboutmisconception; the mean of the pre-test was 48.57. After the action was caried out, the misconception became5.73%. The score of the learning outcome was 73.3. While the score of the students’ scientific attitude was68.24; After the second cycle, there was 53.51% of the prior knowledge of the students was misconception,while the mean score of the pre-test was 63.3. after the action was conducted, the misconception became10.40, while the students response towards the teaching was 78.6. Their scientific attitude was about 75.40,while their response to this teaching were very good. Based on this finding it was suggested that lecturerswho had problems on the students especially to those who had low achievement, and their scientific attitudecould apply the contextual approach to degrade the students misconception. An analysis of the students priormisconception should be done, the result could be used as the basis when designing the teaching program.Key words: contextual teaching and learning, misconception, scientific attitude